The link between childhood traumatic events and the continuum of premenstrual disorders - Standeven, Lindsay R.; Bajaj, Mira; McEvoy, Kathleen; Shirinian, Dalar; Voegtline, Kristin; Osborne, Lauren M.; Payne, Jennifer L.; Hantsoo, Liisa (Frontiers in Psychiatry, 2024)
Background: Premenstrual Syndrome (PMS) and Premenstrual Dysphoric Disorder (PMDD), collectively known as Premenstrual Disorders (PMDs), cause significant distress and functional impairment, and premenstrual exacerbation (PME) affects a large proportion of women with psychiatric diagnoses. Childhood trauma is one factor that may contribute to PMD/PME risk. This study examines the relationship between childhood trauma and PMDs, PME, and non-PMD psychiatric illness.Methods: This study is a secondary analysis of data from a prospective cohort. Participants completed self-assessments on childhood trauma using the Childhood Traumatic Event Scale (CTE-S) and on premenstrual symptoms using the Premenstrual Symptoms Screening Tool (PSST). Psychiatric diagnoses were assessed through structured clinical interviews. Participants were divided into four groups based on their PSST scores and psychiatric illness status: (1) Premenstrual Disorders (PMDs; moderate to severe PMS and PMDD), (2) PME, (3) psychiatric controls (PC; individuals with psychiatric illness but no significant premenstrual symptoms), and (4) healthy controls (HC; individuals with no psychiatric illness and no significant premenstrual symptoms). Statistical analyses, including ANOVA, Tukey's HSD test, Fisher's exact test, and logistic regression, were conducted to examine differences among the groups.Results: Data from 391 participants were analyzed. Participants with PME and PC reported a higher quantity and severity of childhood traumatic events compared to HCs (p < .05). There was a weak but significant correlation between childhood trauma and premenstrual symptom burden across all groups (R = .18, p < .001). Within-group analysis revealed moderate correlations between childhood trauma and premenstrual symptoms driven by the PMD group (R = .42, p = .01). Conclusions: The findings underscore the impact of childhood traumatic events on mental health and premenstrual symptoms and highlight the need for additional research to explore the underlying mechanisms linking childhood trauma to the continuum of premenstrual disorders, to improve the efficacy of trauma-focused interventions for affected individuals.